Adjustment mechanism with sliding mode for adaptive PD controller applied to unmanned fixed-wing MAV altitude - Espinoza-Fraire, A.T.; Saenz-Esqueda, A.; Cortes-Martinez, F. (IAES International Journal of Robotics and Automation (IJRA), 2021)
This work presents an adjustment mechanism with the sliding modes technique to de- sign a proportional derivative (PD) controller with adaptive gains. The objective and contribution are to design a robust adjustment mechanism in the presence of unknown and not modeled perturbations in the system; this perturbation can be considered wind gusts. The robust adjustment mechanism is designed with the MIT rule and the gra- dient method with the sliding mode theory. The adaptive PD obtained is applied to regulate unmanned fixed-wing miniature aerial vehicle (MAV’s) altitude.